Oliguria as a diagnostic marker of severe leptospirosis: a study from the Transcarpathian region of Ukraine - Petakh, Pavlo; Kamyshnyi, Oleksandr (Frontiers in Cellular and Infection Microbiology, 2024)
Leptospirosis is an emerging illness presenting a broad range of clinical manifestations, ranging from asymptomatic or mild cases to severe and fatal outcomes. Early detection is crucial for effective treatment; however, similar clinical presentations in various febrile illnesses or co-infections, along with challenges in laboratory diagnostics, can lead to misdiagnosis and severe consequences. Identifying clinical predictors for severe forms of the disease is essential in mitigating complications and reducing mortality. Consequently, we conducted a retrospective case-control study to identify clinical markers indicative of severe disease in leptospirosis patients from the Transcarpathian region. The study focused on patients admitted with clinically suspected leptospirosis, involving a total of 51 diagnosed cases, with 13 resulting in severe outcomes and death. Categorical variables were analyzed using χ2, revealing a mean patient age of 50 years, predominantly male (n = 36, 70.5%). Oliguria emerged as a significant independent factor associated with mortality (odds ratio [OR], 13.5; 95% confidence interval [CI], 2.56–71.12; p = 0.001). Additionally, our analysis uncovered a noteworthy increase in leptospirosis notification rates in Transcarpathian compared to Ukraine, with 150 cases out of the total 433 in Ukraine. The highest notification rates were observed in Mukachevo District and Perechyn District. These findings highlight the importance of early recognition of key clinical markers, such as oliguria, which are critical for predicting severe outcomes in leptospirosis patients. The higher notification rates in Transcarpathian regions also underscore the need for enhanced surveillance, targeted public health interventions, and timely treatment to reduce mortality in endemic areas.